2006
DOI: 10.1086/504682
|View full text |Cite
|
Sign up to set email alerts
|

Debris Disks around White Dwarfs: The DAZ Connection

Abstract: We present near-infrared spectroscopic observations of 20 previously known DAZ white dwarfs obtained at the NASA Infrared Telescope Facility. Two of these white dwarfs (G29-38 and GD362) are known to display significant Kband excesses due to circumstellar debris disks. Here we report the discovery of excess K-band radiation from another DAZ white dwarf, WD0408-041 (GD56). Using spectroscopic observations, we show that the excess radiation cannot be explained by a stellar or substellar companion, and is likely … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
218
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(227 citation statements)
references
References 32 publications
8
218
1
Order By: Relevance
“…A third shared property among these first half dozen examples is that the infrared excesses all become apparent by 2 − 3 µm, a trait that is now known to be common (but not universal), and hence the most prominent of these are detectable from the ground using K-band spectroscopy (Kilic et al, 2006;Kilic & Redfield, 2007). Although these first several discoveries are likely biased by favoring the bright end of the disk luminosity function, they are highly instructive.…”
Section: Basic Dust Propertiesmentioning
confidence: 98%
“…A third shared property among these first half dozen examples is that the infrared excesses all become apparent by 2 − 3 µm, a trait that is now known to be common (but not universal), and hence the most prominent of these are detectable from the ground using K-band spectroscopy (Kilic et al, 2006;Kilic & Redfield, 2007). Although these first several discoveries are likely biased by favoring the bright end of the disk luminosity function, they are highly instructive.…”
Section: Basic Dust Propertiesmentioning
confidence: 98%
“…These objects have become the subject of renewed interest following the detection of infrared excess radiation indicative of the presence of circumstellar dust (Zuckerman & Becklin 1987;Becklin et al 2005;Kilic et al 2005Kilic et al , 2006Jura et al 2007). Although the spectra from optical to IR can be fairly well modeled with simple disk models (e.g., Jura et al 2007), the exact geometrical distribution was only confirmed with the detection of gaseous metal disks around hotter white dwarfs, which clearly show the signature of Keplerian rotation (Gänsicke et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…An easier way to detect remnant planetary systems around WDs is to look for the tidally disrupted remains of exoplanets, moons, and asteroids in the form of circumstellar debris discs (Debes & Sigurdsson 2002;Jura 2003;Kilic et al 2006;Farihi, Jura & Zuckerman 2009;Veras et al 2013Veras et al , 2014aVeras, Jacobson & Gänsicke 2014b). Consider a planetary system consisting of a WD, an asteroid-belt analogue and a Jupiter analogue.…”
Section: Introductionmentioning
confidence: 99%